Impact Analysis Of National Assignment Projects (PSN) On State-Owned Construction Enterprises As Project Assignment Recipients (A Case Study On The Assignment Of State-Owned Construction Enterprises For The Period 2014-2022) - Vega Alberta; Zuliani Dalimunthe (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to assess the impact on two main aspects: profitability performance and solvency performance of construction state-owned enterprises (BUMNs). It evaluates changes in net profit and related profitability indicators, as well as changes in the debt-to-equity ratio and other solvency indicators during the assignment period. By examining these aspects, the research aims to provide a scientific perspective on how the assignment of national strategic projects affects the financial health of the assigned companies. The study utilizes a case study approach with a descriptive method, focusing on financial data extracted from the annual reports of three BUMNs: PT Waskita Karya (Persero), PT Hutama Karya (Persero), and PT Adhi Karya (Persero). These companies have been tasked with executing National Strategic Projects (PSNs) since 2015. The scope of the study spans from one year prior to the assignment in 2014 to the performance year of 2022. The sample selection is based on the significant roles of these companies in implementing PSNs in Indonesia.The research data includes elements from the companies' financial statements, such as the balance sheet, income statement, and cash flow statement, gathered from annual financial reports accessible through official websites or financial databases. Financial analysis techniques, including Common Size Analysis, Ratio Analysis, Z-Score Analysis, Economic Value Added (EVA), and Du Pont Analysis, will be applied to analyze and compare the financial performance of the three BUMNs throughout the study period. The research findings suggest that PSN assignments had a significant impact on the profitability of PT Hutama Karya (Persero), PT Waskita Karya (Persero), and PT Adhi Karya (Persero). All three companies faced increased financial pressure due to interest burdens, indicating internal financial strains affecting profits. While PT Hutama Karya experienced increased interest burdens, PT Waskita Karya showed limited revenue growth, and PT Adhi Karya witnessed a decline in net income. Solvency varied among the companies, with PT Adhi Karya and PT Hutama Karya demonstrating good short-term liquidity, whereas PT Waskita Karya experienced decreased liquidity. Economic value added decreased for all three companies, reflecting challenges in generating returns equivalent to capital and debt utilized. PT Adhi Karya and PT Hutama Karya improved capital structure, while PT Waskita Karya showed limited improvement.